Købmandskab i tyrker-frygtens tid - Madsen, Peter (K&K - Kultur og Klasse, 2017)
Attempts from the side of the Holy See to undercut commercial relations with the Near Orient were never particularly successful, not even after the Fall of Constantinople when fear of the Turks was on the rise. Two German literary works from the following half century demonstrate how the viewpoint of the merchants is articulated within a horizon of experience that is far from religious or geo-political concerns. In Rosenplüt’s carnival play Des Türken Fastnachtspiel the Turkish Sultan is depicted as representing an idealized state (not least when it comes to the conditions of commerce) contrasting the multifarious deficiencies of the Holy Roman Empire; in the anonymous novel Fortunatus the conditions and institutions of commercial relations are foregrounded, exemplified by Alexandria and with a focus on the rational logic of commerce.